1997
DOI: 10.2169/internalmedicine.36.575
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-Type Human Insulin Allergy Successfully Treated by Continuous Subcutaneous Insulin Infusion.

Abstract: A 63-year-old insulin-dependent diabetic womanwas hospitalized with itchy skin wheals at the injection sites of humaninsulin. After intradermal skin testing was performed, the erythema and wheal was recorded immediately. The increased titer of human insulin-specific IgE antibody indicated immediate-type allergy against humaninsulin. Administration of an anti-allergic drug or desensitization for humaninsulin every 2 hours was not effective. After continuous subcutaneous insulin infusion (CSII) therapy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…This is not the first description of the use of CSII to treat localised insulin allergy in patients with either type 1 or type 2 diabetes, [2][3][4][5][6] and our patient's symptoms were significantly and sufficiently improved rather than cured. However, we are not aware of other examples where i-Port Advance™, a device that has been developed to make it possible for people with needle phobia to be able to inject insulin themselves, has been used for this indication.…”
Section: Discussioncontrasting
confidence: 56%
“…This is not the first description of the use of CSII to treat localised insulin allergy in patients with either type 1 or type 2 diabetes, [2][3][4][5][6] and our patient's symptoms were significantly and sufficiently improved rather than cured. However, we are not aware of other examples where i-Port Advance™, a device that has been developed to make it possible for people with needle phobia to be able to inject insulin themselves, has been used for this indication.…”
Section: Discussioncontrasting
confidence: 56%
“…With the introduction of highly purified recombinant human insulin, allergic reactions to this product have become rare but still persist, with an incidence estimated to be less than 1% [2]. Insulin injected in the subcutaneous tissue may elicit various reactions from the immune system [3].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this initial favourable report, the use of CSII delivering human regular insulin in diabetic patients with insulin allergy when treated with conventional injection therapy remained exceptional, as only one single case has been described with continuous delivery of human insulin [41]. A 63-year-old insulin-dependent diabetic woman was hospitalised with itchy skin wheals at the injection sites of human insulin.…”
Section: Csii and Insulin Allergymentioning
confidence: 99%
“…In contrast, after CSII therapy was performed, both itching and wheal disappeared. The authors concluded that the process may be a desensitisation through CSII and suggested that CSII may be useful in the treatment for human insulin allergy [41].…”
Section: Csii and Insulin Allergymentioning
confidence: 99%